Speech Function in Raditya’s Utterances in Stand Up Comedy Show - Miranda Sari Damanik; Amrin Saragih (LINGUISTIK TERAPAN, 2016)
The objectives of this study are (1) to describe the system network of speech functions dominantly used in Raditya Dika’s utterances in Stand Up Comedy Show, (2) to investigate speech function realized in moods in Raditya Dika’s utterances in Stand Up Comedy Show, and (3) to elaborate the reason the system network of speech function dominantly used. The research applies qualitative descriptive design. The source of data is Raditya Dika in Stand Up Comedy Show program on Metro TV. The research findings show that the system network of speech functions in Raditya Dika’s utterances are statement which was information was the most system network of statement and then followed by furry, disappointment, reason, blame , clarification, support, probability,  hope, call, greeting. The next system network of speech functions dominantly used was question which was Wh-question and then followed by yes/no question. And the last was command. The dominant speech function of command was positive command and then followed by negative command. Statement, question, command, and where statement which realized in tagged declarative mood occurs most dominantly and then question realized by interrogative mood and command realized by imperative mood. The reasons are that every sentence has realized in the speech function and also speech function in semantics has realized in mood system in lexicogrammar. Keywords: interpersonal speech  function, system network